ANTIHYPERTENSIVE ACTIVITY OF QUINOA (Chenopodium quinoa Willd.) PROTEIN HYDROLYSATES - Moreno-Limón, Sergio; González-Luna, Rodrigo (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Nowadays, there has been an increase in the number of studies focused on the search for bioactivecompounds produced by hydrolytic reactions from natural sources, such as the Quinoa grain, which represents aninteresting agro-alimentary source that can have a beneficial influence on health, specifically antihypertensive potential. Forthis reason, the aim of the present study was to evaluate the antihypertensive activity of the protein hydrolysates obtained ofQuinoa, which results important at the time to consider the incorporation of such peptides in the design of functional foods.Materials and Methods: Quinoa (Chenopodium quinoa Willd.) seeds were ground and the obtained flour was degreasedand the protein isolate was obtained by isoelectric precipitation. The protein isolate was enzymatically hydrolyzed withAlcalase® and Flavourzyme® and the antihypertensive effect of peptides against angiotensin converting enzyme wasevaluate using a mixture of 50 μL of sample, 50 μL of ACE working solution, 200 μL of substrate working solution and thefluorescence was determined with a microplate fluorometer following these characteristics: λ (excitation) = 355-375 nm; λ(emission) = 400-430 nm.Results: Peptides obtained using Alcalase® (protein content= 72.13%; DH= 31.22%) showed the highest inhibitoryactivity against the angiotensin converting enzyme (ACE), close to 88%.Conclusion: The Quinoa protein hydrolysates can be considered as a new agri-food source to be incorporated in theelaboration of functional foods with antihypertensive potential.